THE EFFECTIVENESS OF THE STANDARD MEDIA ASSISTED CTL MODEL ON MATHEMATICS LEARNING OUTCOMES - Safitri, Tyas Rima; Trimurtini, Trimurtini (Elementary School Teacher, 2020)
This study aimed to test the effectiveness of contextual teaching and learning model assisted by geoboard on mathematics learning outcomes of area and perimeter subject in the fourth grade at Tamansari Cluster Elementary School Kebumen Regency. The design of this study was quasi-experimental in the form of nonequivalent control group. The population in this study were all the fourth grade students at Tamanwinangun 4 Elementary School as the experimental class and fourth grade students at Tamanwinangun 3 Elementary School as the control class. The data collection techniques used test and non-test techniques. The hypothetical analysis test used the z test, t test and N-gain test. The result showed that the CTL learning model assisted by geoboard was more effective which surpassed 75% of the passing grade while the control class did not reach 75%, tcount (4.06)> ttable (1.67), and n-gain experimental class (0.6529)> control class (0.5078). The conclusion of this research was that the CTL learning model assisted by geoboard was more effective to gain the mathematics learning outcomes in the fourth grade at Tamansari Cluster Elementary School Kebumen Regency.